(untitled) (Research, Society and Development, 2022)
Purpose: The present study evaluated the following caffeoylquinic acids, Neochlorogenic acid (3-CQA), Cryptochlorogenic acid (4-CQA), Chlorogenic Acid (5-CQA), Isochlorogenic acid A (3,5-DCQA) Isochlorogenic acid B (3,4-DCQA) and Isochlorogenic acid C (4,5-DCQA) found in Brazilian green propolis, regarding its physicochemical, pharmacokinetic and conformational characteristics. Additionally, the compounds were explored on the efficacy of inhibiting the pharmacological target SARS-CoV-2 Mpro, a protein involved in SARS-Cov-2 infection. Methods: The physicochemical and pharmacokinetic proprieties were obtained from the projected 2D structures of the respective compounds. The conformational characteristics were obtained from the three-dimensional models were subjected to geometric optimization by molecular mechanics under MMFF94 force field, subsequently, the calculation of partial atomic charges by employing AM1 semi-empirical methodology was performed. Molecular docking was performed, and the protein was loaded in PDB Data Bank (PDB ID 6LU7). Results: The physicochemical and pharmacokinetic results indicate that these phytochemicals have from medium to low potential for gastrointestinal tract absorption, principally in relation to the LogP values, and violated some druglikeness’ criteria. However molecular docking showed that the compounds 3-CQA, 4-CQA, 5-CQA, 3,5-DCQA, 3,4-DCQA and 4,5-DCQA potentially binds with the active site of the SARS-CoV-2 Mpro, through stables complexes, with a docking score of -6.44, -6.11, -6.48, -6.26, -7.01 and -7.40 kcal/mol, respectively. Conclusion: The physicochemical and pharmacokinetic parameters, as well as Hydrogen-bond formation, energy landscape, indicate that the compound with the greatest therapeutic potential are 5-CQA, 3,4-DCQA and 4,5-DCQA however this study necessitates further in vitro and in vivo experimental validation.